Entre la espada y la pared : pedagogías de la sexualidad en torno a moral sexual, prostitución y formación de masculinidades en Costa Rica - Varela, Luis Pablo Orozco (2016)
Through a tour of the streets of San Jose, Costa Rica, and its territories destined for the sex trade by men for men, we have arrived at the National Park, where this research is produced based on a study of the formation of masculinity between sex workers who go that place. In that sense, we inspired ourselves from the theoretical contributions that come from several aspects of post-structuralism besides theories of gender and "queer" theory of performativity in discourses on the formation of subjectivities, among others. In terms of methodology, we try to approach the contributions of the ethnographic method, operating with interviews with young sex workers themselves, among other places, participant observation, reading news published in newspapers, questioning of speeches and performances on sex tourism in the country, among others. When we investigate a matter that involves the formation of masculinity and sex work, possibly, it is the metaphor of who walk through mined areas, routes through tension, where circulate discourses of hegemonic sexual culture that is fundamentally "heteronormative" and is based on the values of Catholic Christianity and intersect with testimonies of struggle, solidarity, violence, decisions, projects of future life once ends sex work and other experiences that relate to the biographies of the boys who prostitute themselves in the National Park of San José, Costa Rica.